Experimental evidence of the production of inflected infinitives by Brazilian Portuguese speakers - Modesto, Marcello; Soto, Marije; Improta França, Aniela (Revista da ABRALIN, 2022)
The Minimalist Program launched by N. Chomsky (1995) inspired reductionist accounts of Control phenomena, which tried to eliminate ‘PRO’ from the theory of grammar, treating it as a trace (copy) of movement (Martin 1996; O’Neil 1997; Hornstein 1999 et seq.). Such movement theories of Control are directly challenged by the use of inflected infinitives in Brazilian Portuguese (BP), as shown in Modesto (2010). Many supporters of the movement theory, however, have denied the empirical argument, making the claim that inflected infinitives “are not natural in BP” (Rodrigues & Hornstein 2013: 307), not belonging to BP’s “core grammar”. This study, then, presents two experiments in which production of nonfinite inflection is implicitly elicited in a pseudoword oral completion task. Participants from different linguistic geographic varieties (the cities of Rio de Janeiro and São Paulo) heard the pseudoverb in its gerundive form and were then prompted to insert the pseudoverb in a sentence frame that would be compatible with both uninflected and inflected infinitive forms. Our results show 73.3% of participants inflected the infinitive to some degree when indirectly primed to do so, and that 40.9% did so, even when not primed. Results also show that while linearly distant plural markings (on the subject) did not influence behavior, adjacent morphosyntactic plural markings (on secondary predicates, for instance) did slightly increase the probability of inflection. Both priming effects and sensitivity to morphosyntactic context seem to indicate that nonfinite inflection is a productive, albeit variable, feature of BP speakers’ I-grammar.